Bioeconomic analysis of the production of marine shrimp in greenhouses using the biofloc technology system - de Almeida, Marcos Souza; Carrijo-Mauad, Juliana Rosa; Gimenes, Régio Marcio Toesca; Gaona, Carlos Augusto Prata [UNESP]; Furtado, Plínio Schmidt; Poersch, Luís Henrique; Wasielesky, Wilson; Fóes, Geraldo Kipper (Springer Nature, 2021)
This study analyzes the investment in Penaeus (Litopenaeus) vannamei shrimp production in greenhouses using the biofloc technology system (BFT). Considering bioeconomic variables, a sensitivity analysis was performed with data collected over the course of 10 years to evaluate program efficiency. The parameters considered include a stocking density of 400 shrimp/m2, which reached a productivity rate of 3.84 kg/m2 (69,120 kg/year—three cycles), a final mean weight of 12 g, and a feed conversion rate of 1.3. The results obtained had a net present value (NPV) of US$ 904,947.21, net future value (NFV) of US$ 2,401,094.35, equivalent annual value (EAV) of US$ 148,861.38, payback (PB) of 2 years and 4 months, discounted payback period (DPP) of 2 years and 10 months, profitability index (PI) of 2.59, internal rate of return (IRR) of 41.23%, and a modified internal rate of return (MIRR) of 21.25%. However, shrimp with a final mean weight of 15 g resulted in an NPV of US$ 2,522,150.62, NFV of US$ 6,692,016.44, EAV of US$ 414,886.98, a PB of 1 year and 2 months, DPP of 1 year and 2 months, PI of 5.43, IRR of 89.13%, and an MIRR of 30.57%. The Monte Carlo simulation (MCS) concluded that the probability of NPV being negative is 0. The analysis confirms that P. vannamei production using the BFT system is a financially sustainable activity.
Keywords: Biofloc technology; Investment analysis; Litopenaeus vannamei; Monte Carlo simulation; Net present value; Payback